Daya Tarik Iklan Dan Relevansi Pesan Iklan Terhadap Sikap Dan Minat Beli - Nurul Izzah Karimah; Diah Kusumawati (Universitas Sebelas Maret (UNS), 2024)
The purpose of this research is to examine the level of interest in the Marjan Baruna Sang Penjaga Samudera advertisement regarding the elements contained in the advertisement which can influence viewers' attitudes and buying interest. To evaluate this research, the Elaboration Likelihood Model theory from Petty & Cacioppo (1986) was used. This research uses quantitative methods, with 97 research samples. The data collection technique used a questionnaire which was given to a number of respondents taken from Marjan Boudoin's YouTube comments column on the Marjan Baruna Sang Penjaga Samudera version of the advertisement. Meanwhile, to analyze the data, PLS-based SEM analysis techniques were used. The results show that the attractiveness of the advertisement influences attitudes towards the advertisement, the attractiveness of the advertisement influences attitudes towards the product, the attractiveness of the advertisement influences the interest in purchasing the product, the relevance of the advertising message does not influence attitudes towards the advertisement, the relevance of the advertising message does not influence attitudes towards the product, the relevance of the advertising message does not influence the intention to buy the product, the attitude towards the advertisement does not influence the attitude towards the product, and the attitude towards the product influences the intention to buy the product..